PENGARUH KOMBINASI PROSES TERMAL DAN JENIS KEMASAN TERHADAP MUTU CIMPLUNG SINGKONG SIAP SAJI - Abdul Mukhlis Ritonga (Program Studi Teknik Pertanian, Fakultas Pertanian, Universitas Jenderal Soedirman, 2022)
Cassava cimplung is a traditional processed food made from cassava which is boiled in coconut sap water. Cassava has not been widely produced in ready-to-eat packaging as a selling value food. This is because cimplung is a semi-wet food so it easily spoils and does not last long. In an effort to maintain the quality of cassava cimplung, in this study a thermal pasteurization process was carried out with variations in the length of 10 minutes and 15 minutes and the use of EVOH (Ethylene Vinyl Alcohol) and boilpack packaging. Quality parameters observed included texture, pH, color, and brix content for 6 weeks of storage. The aims of this study were 1) To determine the effect of packaging type on the quality of cassava cimplung, 2) To determine the effect of pasteurization time on the quality of cassava cimplung, and 3) To determine the interaction effect of packaging type and pasteurization duration on the quality of cassava cimplung. The results of this study were 1)The treatment of the type of packaging was significantly different on the value of texture, pH, and color but was not significantly different on the brix content of cassava cimplung, 2) Pasteurization time treatment was significantly different to color value but not significantly different to texture, brix content, and pH of cassava cimplung, and 3) The interaction between the type of packaging and the duration of pasteurization was not significantly different on all quality parameters of cassava cimplung